1983
DOI: 10.1111/j.1365-2125.1983.tb04984.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of evidence for polymorphism in metoprolol metabolism.

Abstract: The claim for polymorphism in the metabolism of metoprolol is based on a logical fallacy. A frequency distribution of metoprolol AUC data is presented and, although highly skewed, no evidence of more than a single population is apparent. Plasma and urine metoprolol and metabolite data are also presented to support this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1983
1983
1991
1991

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…It was found that for metoprolol, timolol, propranolol and atenolol, 94, 61,8 and 0%, respectively, of the variance in AUC was related to the debrisoquine to 4-hydroxydebrisoquine ratio. However, Jack et al (1983a) have argued that the metabolism of metoprolol is not polymorphic since there is no evidence of bimodality in the frequency distribution of its AUe. With the aid of a computer simulation Jackson et al (1984, and in preparation) have shown that the use of AUC data is an insensitive method for detecting genetic polymorphism when the defect is present in only a small proportion of the population ( fig.…”
Section: Contribution Of Oxidation Phenotype To Variability In Pharmamentioning
confidence: 97%
“…It was found that for metoprolol, timolol, propranolol and atenolol, 94, 61,8 and 0%, respectively, of the variance in AUC was related to the debrisoquine to 4-hydroxydebrisoquine ratio. However, Jack et al (1983a) have argued that the metabolism of metoprolol is not polymorphic since there is no evidence of bimodality in the frequency distribution of its AUe. With the aid of a computer simulation Jackson et al (1984, and in preparation) have shown that the use of AUC data is an insensitive method for detecting genetic polymorphism when the defect is present in only a small proportion of the population ( fig.…”
Section: Contribution Of Oxidation Phenotype To Variability In Pharmamentioning
confidence: 97%
“…These metabolites possess about one-tenth the i3-blocking activity ofmetoprolol (Borg et al 1975). Genetic polymorphism in metoprolol metabolism was not observed (Horai et al 1989;Jack et al 1983). These data suggest that these active metabolites do not usually contribute to the i3-blocking activity.…”
Section: Pharmacokinetic Datamentioning
confidence: 99%
“…This was also shown to be the case for one minor metabolic pathway of the first available beta blocker propranolol (Lennard el al, 1986) as well as for bufuralol (Dayer et al, 1985) which was never introduced as a drug. There was an unusual debate about the presence or absence of bimodality of metoprolol clearance (Jack et al, 1983;Jack and Wilkins, 1984;Lennard et al, 1984;Idle and Smith, 1984;Regirdh and Johnsson, 1984) but it was unequivocally established that low clearance of metoprolol is related to the phenotype poor metaboliser of debrisoquine (Lennard et al, 1982(Lennard et al, , 1983a. In figure 5 , the relationship between metoprolol plasma concentrations and beta blockade in four rapid metabolisers and in 6 slow metabolisers of debrisoquine is shown in plasma samples drawn at 2, 12 and 24 h after dosing.…”
Section: Beta Blockersmentioning
confidence: 99%